Comparison of central-line–associated bloodstream infections between central venous catheters lined by combined chlorhexidine and silver sulfadiazine versus silver ionotrophes alone: A before–after–before retrospective study. (11th February 2021) - Abouleish, Youssef Z.; Oldfield, Edward C.; Marik, Paul E.
Abstract: A before–after–before direct comparison between catheters lined with chlorhexidine and silver sulfadiazine (CHSS) versus silver ionotrophes (SI) with a primary objective of comparison of rate of central-line–associated infection (CLABSI) in three 10-month windows. The CHSS catheters were associated with a lower rate of CLABSI.